Catheter with dielectric optical filter deposited upon the fiber optic end for Raman in vivo biospectroscopy applications. Issue 6 (2008) - de Lima de Lima, Carlos José Carlos José; Pacheco Pacheco, Marcos Tadeu T. Marcos Tadeu T.; Villaverde Villaverde, Antonio Balbin Antonio Balbin; Zângaro Zângaro, Renato Amaro Renato Amaro; Moreira Moreira, Leonardo Marmo Leonardo Marmo; Damião Damião, Álvaro José Álvaro José
Abstract : Raman spectroscopy (RS) is a powerful tool that allows obtaining significant biochemical information from biological tissue. The fiber optic catheter permits applications in vivo that present wide clinical employment. This biochemical analysis is developed through a guide light that furnishes to Raman spectroscopy system the data obtained from tissue. These Raman signals represent the modes of vibration of molecular groups that are present in the biological molecules. Raman measurements undergo the optical influence of the material that constitutes the catheter, mainly Raman scattering of the silica that composes the fiber optic, decreasing signal to noise ratio (SNR) of the resultant spectra. In this work, a dielectric optical filter called "bandpass" was deposited upon the surface of the tip of the central fiber optic (distal probe). Indeed, other six fibers without any optical filter are disposed around this central optical fiber with "bandpass". This prototype of catheter presented significant decrease of the silica Raman scattering when compared with unfiltered catheters. The biomedical applications of this new catheter are auspicious, involving biochemical analysis and diagnosis in vivo, since the SNR improvement obtained propitiates a much more informative Raman spectrum.